Hot subdwarf stars in close-up view: II. Rotational properties of single and wide binary subdwarf B stars - Geier, Stephan; Heber, Ulrich (Astronomy & Astrophysics, 2012)
Subluminous B stars (sdBs) form the extremely hot end of the horizontal branch and are therefore related to the blue horizontal branch (BHB) stars. While the rotational properties of BHB stars have been investigated extensively, studies of sdB stars have concentrated on close binaries that are influenced by tidal interactions between their components. Here we present a study of 105 sdB stars, which are either single stars or in wide binaries where tidal effects become negligible. The projected rotational velocities have been determined by measuring the broadening of metal lines using high-resolution optical spectra. All stars in our sample are slow rotators (v rotsini < 10< kms -1). Furthermore, the v rotsini-distributions of single sdBs are similar to those of hot subdwarfs in wide binaries with main-sequence companions as well as close binary systems with unseen companions and periods exceeding ≈ 1.2< d. We show that blue horizontal and extreme horizontal branch stars are also related in terms of surface rotation and angular momentum. Hot BHB stars (T eff > 11 500< K) with diffusion-dominated atmospheres are slow rotators like the hot subdwarf stars located on the extreme horizontal branch, which lost more envelope and therefore angular momentum in the red-giant phase. The uniform rotation distributions of single and wide binary sdBs pose a challenge to our understanding of hot subdwarf formation. Especially the high fraction of helium white dwarf mergers predicted by theory seems to be inconsistent with the results presented here. © 2012 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; Stars: rotation; Subdwarfs